Comparative Assessment of TSPO Modulators on Electroencephalogram Activity and Exploratory Behavior - Hines, Rochelle M.; Aquino, Elaine A.; Khumnark, Matthew I.; Dávila, Maria P.; Hines, Dustin J. (Frontiers in Pharmacology, 2022)
Network communication in the CNS relies upon multiple neuronal and glial signaling pathways. In addition to synaptic transmission, other organelles such as mitochondria play roles in cellular signaling. One highly conserved mitochondrial signaling mechanism involves the 18kDa translocator protein (TSPO) of the outer mitochondrial membrane. Originally, TSPO was identified as a binding site for benzodiazepines in the periphery. It was later discovered that TSPO is found in mitochondria, including in CNS cells. TSPO is implicated in multiple cellular processes, including the translocation of cholesterol and steroidogenesis, porphyrin transport, cellular responses to stress, inflammation, and tumor progression. Yet the impacts of modulating TSPO signaling on network activity and behavioral performance have not been characterized. In the present study, we assessed the effects of TSPO modulators PK11195, Ro5-4864, and XBD-173 via electroencephalography (EEG) and the open field task (OFT) at low to moderate doses. Cortical EEG recordings revealed increased power in the δ and θ frequency bands after administration of each of the three modulators, as well as compound- and dose-specific changes in α and γ. Behaviorally, these compounds reduced locomotor activity in the OFT in a dose-dependent manner, with XBD-173 having the subtlest behavioral effects while still strongly modulating the EEG. These findings indicate that TSPO modulators, despite their diversity, exert similar effects on the EEG while displaying a range of sedative/hypnotic effects at moderate to high doses. These findings bring us one step closer to understanding the functions of TSPO in the brain and as a target in CNS disease.